Environmental Graphic Design for The MPU Tantular Museum Using a Design Thinking Approach - Prasetya, Ardian Jaya; Yurisma, Dhika Yuan (Future Science, 2023)
Visitors to the MPU Sidoarjo Tantular Museum are dominated by school students who have assignments from school. The lack of information on each museum collection causes visitors to be less interested in visiting. This research aims to design environmental graphic designs as a branding effort for the Mpu Tantular Sidoarjo museum. The design is made in the form of wayfinding and museum signage. The method used in this research is Design Thinking with a basic scheme, namely Emphatize, define, ideate, prototype, test. direct data mining through observation and interviews. From the results of data analysis, a concept was obtained to design a prototype environmental graphic design so that visitors can improve their experience of visiting the MPU Tantular museum. Media implementation using sticker material. In the future, we suggest that this research can be developed using the latest technology such as virtual reality to improve visitor experiences.